The Influence of Regional Dialects on Students’ Arabic Speaking Skills at Pondok Pesantren Darussalam Al-Hafidz Jambi City - Reski Lespander; Helmun Jamil; Rofiazka Fahmi Huda (STKIP Subang, 2026)
This study examines the influence of regional dialects on students’ Arabic speaking skills at Pondok Pesantren Darussalam Al-Hafidz, Jambi City. The research aims to identify the extent to which dialectal background affects pronunciation accuracy, intonation, and fluency, as well as to explore the factors contributing to phonological interference. A descriptive qualitative approach was employed, with data collected through classroom observations, interviews, pronunciation tests, and documentation. The findings indicate that regional dialects significantly influence students’ Arabic speaking performance, particularly in the early stages of language acquisition. This influence is evident in phonological interference, where students tend to mispronounce certain Arabic sounds that are absent in their native languages, affecting clarity and communicative effectiveness. Several contributing factors were identified, including differences in phonological systems, strong attachment to the mother tongue, psychological aspects such as low self-confidence, and varying levels of practice intensity. However, the study also reveals that dialectal interference is not permanent. Continuous exposure to Arabic, regular speaking practice, and a supportive learning environment contribute to gradual improvement in pronunciation and fluency. These findings suggest that regional dialect influence is a natural part of second language acquisition and can be minimized through consistent training and immersive language practices. The study highlights the importance of pedagogical strategies that emphasize phonetic awareness and active language use in enhancing students’ Arabic speaking skills.